Guidelines for Creative Ecotourism Management of Bang Pu Community, Pattani Province, Thailand - et. al., Jutatip Junead, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objectives of this research were to 1) to study and analyze the potential of ecotourism resources of Bang Pu community, Pattani Province, 2) to study the needs of stakeholders to the creative ecotourism management of Bang Pu community, Pattani Province, 3) to study behavior and the needs of the Thai eco-tourists towards the ecotourism management model, and 4) to develop products and creative ecotourism activities of the Bang Pu community, Pattani Province.This mixed methods research applied the concept of ecotourism, creative tourism, development of tourism resources, participatory development, and tourism decisions as the research framework. The research area was Bang Pu district, Pattani province. The sample group consisted of 385 Thai ecotourists who were selected by the convenience sampling method. The key informants were 50 local stakeholders who were selected by the purposive sampling and snowball sampling methods. An in-depth interview and participant observation were used to collect the data. There were 5 types of research instruments which are: 1) questionnaires 2) the resource check list by using SWOT Analysis. 3) Diversity Index Survey, and 4) Researcher Interview Form. 5) The quantitative data were analyzed by basic statistics such as Percentage, Means, Standard Deviation, and Inferential Statistics such as T-Test, One-Way Analysis of Variance (ANOVA), Chi Square Test. The qualitative data were analyzed with the content analysis and descriptive writing methods. The results illustrated that the potential ecotourism resources included mullet, scats, eeltail catfish, bass, stingray, egret, Cormorant, Asian openbill, kingfisher, and Brahminy kite. Furthermore, the first demand of the local stakeholders for development wasthe provision of tourism activities and stations to be consistent with Islamic principles, followed by tourism management and safety. The results also showed that Thai tourists had a high level of demand for ecotourism. Guidelines for the creative ecotourism management of Bang Pu Community, Pattani Province based on the results of the analysis of the potential resources of creative ecotourism of Bangpu Community, Pattani Province. It is a creative ecotourism destination. Therefore, the researcher has recommendations for the development of 7 areas, which are as follows, 1) Tourism locations and attractions 2) Accessibility 3) Accommodation 4)Facilities 5)Tourism activities 6) Management 7) Aspect of community participation.